2008
DOI: 10.1097/icu.0b013e3282f2d7a3
|View full text |Cite
|
Sign up to set email alerts
|

Patient-centered care and refractive cataract surgery

Abstract: Cataract surgery has expanded into the realm of refractive surgery and there is a new emphasis on patient-centered care and an optimization of the refractive outcome of the procedure. This trend will continue as newer presbyopic correcting intraocular lenses become available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 15 publications
0
16
0
2
Order By: Relevance
“…Patient preferences also help inform clinical decisions where science has yet to provide dominant solutions to healthcare problems. A patient's belief, attitude and importantly values that may influence his preferences for outcomes and risk of treatments, are vital for effective patient-physician communication [5,[87][88][89][90][91][92][93][94]. Broadly, the methods to assess the preferences fall into either revealed preference or stated preference.…”
Section: Patient Centered Care-patient Reported Outcomesmentioning
confidence: 99%
“…Patient preferences also help inform clinical decisions where science has yet to provide dominant solutions to healthcare problems. A patient's belief, attitude and importantly values that may influence his preferences for outcomes and risk of treatments, are vital for effective patient-physician communication [5,[87][88][89][90][91][92][93][94]. Broadly, the methods to assess the preferences fall into either revealed preference or stated preference.…”
Section: Patient Centered Care-patient Reported Outcomesmentioning
confidence: 99%
“…[1][2][3] Patients implanted with MF IOLs commonly report glare and halos that cause them problems during driving at night. [4][5][6] In one prospective randomized trial MF IOL patients required on average about 0.20 log units (2 dB) or about 30% more contrast to achieve the same acuity level as monofocal IOL patients. 6 Research has shown that there are links between visual problems and crash involvement, self-reported driving difficulties, poor driving simulator performance, and poor on-road driving.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, cataract surgery has developed more of a refractive focus with patients developing high expectations for excellent uncorrected postoperative visual acuity. 1 The goal of modern cataract surgery is to achieve emmetropia or at least a predicted balance with the fellow eye. The spherical component can be achieved by selecting the proper intraocular lens (IOL) implant base upon accurate assessment of axial length and corneal power.…”
Section: ' Introductionmentioning
confidence: 99%